THE EFFECTS OF LEADERSHIP, SCHOOL CLIMATE, AND MANAGEMENT EFFECTIVENESS TOWARD TEACHER PERFORMANCE ON MADRASAH TSANAWIYAH IN BEKASI CITY - AULIA, RAHMAT (PPs UNJ, 2016)
The purpose of this study is to determine the effects of leadership, school climate, and management effectiveness, toward teacher performance in Madrasah Tsanawiyah in Bekasi city. This research tries to answer the problems about teacher performance to increase of learning quality. The research was conducted on teacher performance involving samples of 120 teachers that had been selected from the target population of 285 teachers by using quantitative approach with path analysis method. The research tests hypothesis: (1) leadership had a direct positive effect on teacher performance; (2) school climate had a direct positive effect on compotence of pedagogic; (3) management effectiveness had a direct positive effect on teacher performance; (4) leadership had a direct positive effect on management effectiveness; (5) school climate had a direct positive effect on management effectiveness. Therefore, to improve the teacher performance of madrasah tsnawiyah in city Bekasi, who need to increase the leadership of principal, the school climate, and the management effectiveness.